Peran dan Fungsi Kader, Dukungan Sosial Suami, dan Pengetahuan Tentang Budaya Keluarga pada Pelaksanaan Keluarga Sadar Gizi (Roles and Functions of Cadre, Husband Social Support, and Knowledge of Family Culture on the Implementation of Nutrition Conscious - Ika Murni Saputri; Sulistiyani Sulistiyani; Ninna Rohmawati (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Family that is aware of nutrients is family that all members having good nutrition behavior. Pesanggaran was first place in Banyuwangi which has the lowest of implementation nutrition conscious family, it was 43,3%. The purpose of this study was to analyze the correlation between roles and functions of cadre, husband social support, and knowledge of family culture with the implementation of nutrition conscious family which was held July-August 2015 and used cross sectional approach. The research sample consists of 80 families. The result showed implementation of nutrition conscious family in region of Pesanggaran Public Health Centre was 35%. Based on bivariate analysis, it was found that roles and functions of cadre in the increasing in maternal health, baby, toddler, and socialization Kadarzi, husband social support (emotional, award, instrumental, infoemative), and knowledge of family culture had a significant relationship with the impleentation of Knutrition conscious family.The role and function of cadre in a socialization Kadarzi was the most dominant factor related to implementation of Knutrition conscious family on the family of toddler. Keywords: Kadarzi, toddler, risk factor